Expats and citizens : Managing diverse teams in the Middle East. - Forstenlechner, Ingo (Team Performance Management: Volume 16, Edition 5 & 6., 2010)
This e-book aims to describe the setting of labour markets in the Arabian Gulf as the basis for the understanding the relationship between expatriates and the Indigenous workforce. It also examines the future of the expatriate-citizen relationship and suggestions for future research in this area and provides valuable insights from new perspectives on the theme of managing diverse teams in the Middle East. This e-book expands the understanding of a truly underrepresented topic.